Pengembangan Materi Ajar Cerita Pendek Berbantuan Media Aplikasi Kinemaster di Kelas IX SMP Swasta Jambi - Yusniati Zai (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This research objectives to decide the approach of developing brief tale teaching substances assisted through the Kinemaster software media in class IX SMP and to determine the feasibility of products produced the use of the Kinemaster utility for short story material in elegance IX SMP. This research makes use of research and development methods using the Borg and Gall method with stages of dreams and problem assessment, product layout, product improvement, product validation, product revision, and product testing. The feasibility value calculation is decided the usage of a Linkert scale based totally on the validation effects of material experts and media experts. The fabric development technique was completed to feature several contributions in developing the prevailing quick story textual content cloth into even higher ceren textual content material. The studies outcomes display that the product due to the research "development of brief story coaching substances Assisted via Kinemaster utility Media in magnificence IX of Jambi non-public center faculties" is included in the "super" class. that is based on the effects of fabric professional validation with a score of ninety% in the "superb" class and media professional validation with a rating of 80% inside the "exquisite" category, similarly to an evaluation with the useful resource of Indonesian language instructors with a score of 80 4% in the "top notch" magnificence. ” and additionally the evaluation outcomes from students with a score of 92% in the “excellent” category. for that reason, the product is asserted appropriate to be used within the studying system.